Pengaruh Koneksi Politik dan Tarif Efektif Pajak terhadap Kinerja Keuangan dengan Pergerakan Harga Saham sebagai Pemoderasi - Sirait, Swanto (Media Akuntansi Perpajakan, 2021)
The purpose of this study is to analyze the effect of political connections and effective tax rates on financial performance by moderating stock price movements. The research was conducted in the food and beverage sector which is listed on the Indonesia Stock Exchange. The analytical method used is Multiple Regression analysis accompanied by a moderating effect. The research data was obtained from the Indonesia Stock Exchange website www.idx.co.id which took the financial statements of companies in the food sector from 2015-2019. The results of the study prove that political connections have a significant effect on financial performance. Stock price movements are able to moderate the influence of political connections on company performance. Meanwhile, the effective tax rate has no effect on the company's performance. Stock price movements are not able to moderate the effect of the effective tax rate on company performance.Keywords: Political Connection, Effective Tax Rate, Financial Performance, Stock Price Movement.